Molly and the movie star - Tripp, Valerie, 1951- (The American girls collection, 2000)
Molly is eager to meet a famous movie star at a War Bond rally, until she cannot find the money that her class had collected to buy a bond. Includes information on movies during World War II and a recipe for popcorn.